Interactive Sand Table Design to Train Fine Motor Skill for Children with Neurological Disorders - Haris, Muhammad Fuad Al; Lesmana, I Putu Dody (Politeknik Negeri Malang, 2023)
In this article, design of interactive sand table with watersheds modelling was reported. The prototype of an interactive sand table was designed to train fine motor skill for children with neurological disorders. The hands-on interactive sand table allowed users to create some interactive topographic models by shaping real beach sand which is augmented in real time by an elevation color map, topographic contour lines, and simulated water. A topographic model was generated from the projection of elevation maps and contour line colors that resembled sand topographic conditions using a depth sensor from Microsoft Kinect 360 camera, simulation and visualization tools, and a video projector. The interactive sand table had been successfully demonstrated without adverse events by constructing a miniature of island and watershed topography containing lines of contour, rivers, mountains, plateau, and low land for providing various challenges to the users using sand play experience.